Synthesis, antitumor evaluation and molecular modeling study of novel benzimidazoles and pyrazinobenzimidazoles - Ahmed A. B. Mohameda, Farid A. Badriab, Azza R. Maaroufa, Naglaa I. Abdel-Aziza, Fardous ElSendunyc, Alaa A.M. Abdel-Aziza , d, Said M. Bayomia (Journal of Applied Pharmaceutical Science, 2017)
Some novel benzimidazole and pyrazinobenzimidazole derivatives 5-8 was designed for evaluation of their in vitro cytotoxicity studies using MTT-based assay against three cancer cell lines namely, human hepatoma cell line (HepG2), human breast cancer cell line (MCF-7) and kidney of African green monkey (Vero B). Compounds 5a and 5c-e exhibit the highest and broad spectrum activities against all of the three cell lines tested when compared with reference drug 5-Fluorouracil (5-FU). 1-(1H-Benzimidazol-2-yl)-3-phenylprop-2-en-1-one 5a showed superior and great potency and lethal effect against HepG2, MCF-7 and Vero B cell lines with IC50 values of 2, 1.8 and 3.5µg/ml, respectively, comparable to 5-FU (IC50 values of 62, 12 and 13µg/ml, respectively). Moreover, compound 7b showed potent activity against MCF-7 and Vero B cell lines with IC50 values of 2 and 2.5µg/ml, respectively. Docking study of compounds 5a and 7b into the ATP binding site of epidermal growth factor receptor (EGFR) revealed comparable binding manner to an EGFR inhibitor, Erlotinib.
Keywords: Prop-2-en-1-one.Benzimidazoles. Synthesis. Antitumor effect. Molecular modelling.